MEDIATION IN ENFORCEMENT PROCEEDINGS: APPLICATION IN THE EUROPEAN COUNTRIES AND PROSPECTS OF APPLICATION IN THE RUSSIAN FEDERATION - I. A. Filipova; V. V. Filipov (Russian Journal of Economics and Law, 2017)
Objective: to explore the possibilities of mediation as a method of conflict resolution at the stage of enforcement proceedings in the Russian Federation taking into account foreign experience.Methods: comparative legal method as the main method, also used formal-legal, systemic-structural methods, method of interpretation of legal norms.Results: analysis of the use of mediation at the stage of enforcement proceedings in foreign countries held. The possibility of mediation at the stage of enforcement proceedings in Russia is confirmed. Conditions for effective use of mediation in the field of enforcement proceedings are listed. Proposals for legal regulation of the use of mediation at the stage of enforcement proceedings in Russia are formulated.Scientific novelty: comprehensive study of foreign experience of mediation at the stage of enforcement proceedings on the example of member States of the European Union and the member States of the Eurasian Economic Union, as well as analysis of Russian legislation allow to assess the prospects of mediation in the stage of enforcement proceedings and to identify risks of its use in Russia.Practical significance: the main provisions and conclusions of the article can be used by experts to formulate proposals for the further revision of the State program of the Russian Federation "Justice", approved by Resolution of the Government of the Russian Federation, 15 April 2014 No. 312.